Better to give than to receive: predictive directional measurement of volatility spillovers - Francis X. Diebold; Kamil Yilmaz (TÜSİAD-Koç University Economic Research Forum, 2010)
Using a generalized vector autoregressive framework in which forecast-error variance decompositions are invariant to variable ordering, we propose measures of both total and directional volatility spillovers. We use our methods to characterize daily volatility spillovers across U.S. stock, bond, foreign exchange and commodities markets, from January 1999 through September 2009. We show that despite significant volatility fluctuations in all four markets during the sample, cross-market volatility spillovers were quite limited until the global financial crisis that began in 2007. As the crisis intensified so too did the volatility spillovers, with particularly important spillovers from the bond market to other markets taking place after the collapse of Lehman Brothers in September 2008.
Keywords: G1; F3; 330; Asset Market; Asset Return; Stock Market; Market Linkage; Financial Crisis; Contagion; Vector Autoregression; Variance Decomposition; Kapitalertrag; Börsenkurs; Finanzmarktkrise; Ansteckungseffekt; Dekompositionsverfahren; Welt